Reduced graphene oxide-induced crystallization of CuPc interfacial layer for high performance of perovskite photodetectors. Issue 7 (29th January 2019) - Zou, Taoyu; Zhang, Jianqi; Huang, Shuyi; Liu, Chenning; Qiu, Renzheng; Wang, Xiaozhi; Wu, Wei; Wang, Hai; Wei, Zhixiang; Dai, Qing; Liu, Chuan; Zhang, Shengdong; et al.
Abstract : TS-CuPc/rGO nanocomposite thin films were synthesized and applied as an interfacial layer for high-performance perovskite-based photodiodes. Abstract : Perovskite-based photodetectors have great potential in light-signal conversion; the suppression of the dark current is regarded as one of the main concerns within the academic research communities to achieve a high-performance photodetector. Interfacial engineering in the transport layer is considered as one of the most essential methods for enhancement of perovskite photodetectors. Here, a nanocomposite thin film of tetra-sulfonated copper phthalocyanines and reduced graphene oxide (TS-CuPc/rGO) was investigated as the interfacial layer in perovskite-based photodetectors. Photodetectors with the TS-CuPc/rGO thin film as the interfacial layer exhibited a low dark current density of 2.2 × 10 −8 A cm −2 at bias of −0.1 V as well as high responsivity and detectivity of ∼357 mA W −1 and ∼4.2 × 10 12 jones, respectively; moreover, we observed an ON/OFF ratio of 7.33 × 10 3 to 520 nm light with an intensity of ∼0.077 mW cm −2 . Our study revealed that with rGO additives, TS-CuPc molecules were favorable for the formation of an edge-on stacking film with high crystallinity. The rGO-induced crystalline TS-CuPc thin film with lower crystallographic defects effectively reduced the carrier recombination rate at the interfaces, leading to a suppressed dark current and enhanced photocurrent in the photodetector device, when compared to the less crystalline TS-CuPc layer.